PENERAPAN KONSEFP SHADIQ DAN AL-SHIDDIQ MENURUT PERSPEKTIF Al-QUSYAIRI: Telaah Penafsiran Al-Qusyairi Dalam Tafsir Lathoif al-Isyarat - Zaki, Muhammad; Sugiarto, Fitrah (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2024)
In Sufism discourse, the concept of shadiq and al-shiddiq is an important and fundamental foundation for Sufism experts to begin their spiritual journey. The phenomenon of dishonesty is a very factual thing that is found today. This dishonesty will give birth to corruption, academic fraud, hoax news, fraud and so on. So this paper tries to provide a description of the interpretation of isyari carried out by al-Qusyairi on verses related to the concept of shadiq and al-shiddiq from the interpretation that leads to the interpretation of isyari. The research method that the author uses in this journal article is a qualitative descriptive study of a library research nature taken from books that are in accordance with the study of this journal article and other literature as the main object in this journal. In Tafsir al-Qusyairi Lathoif al-Isalun's explanation of the concepts of shadiq and al-shiddiq, it seems to reflect the tendency to try to reveal the inner meaning and Sufistic practices in the Qur'an, not only revealing the zahir meaning of the verses contained within but inviting us to use intuition to reveal the meaning behind the verses.